Sharing library resources in technology-enhanced and technology-starved times: A Case of Selected Southern African Library Consortiums - Collence T., Chisita; Fombad, Madeleine (ADA University Library, 2024)
Library resource sharing has become the cornerstone of survival and international cooperation. At a time when institutional insularity has given way to convergence, libraries have exploited the advantages proffered by digital technologies to enhance cooperation and collaboration to meet the ever-increasing dynamic and diverse information needs of users. Library resource sharing has become the new currency for leveraging library services beyond time and space. In the face of underfunding, libraries in Southern Africa have thrived through cooperation and collaboration to provide greater access to resources. The study examines the architectural framework of resource sharing among academic libraries in selected Southern African countries. By analyzing the digital divide from a qualitative perspective, the study identifies strategies for enhancing resource sharing between academic libraries and National Research and Education Networks (NRENs) as well as commercial Internet Service Providers (ISPs).The proliferation of NRENs has come at an opportune time when most academic libraries in Southern Africa are involved in resource sharing using digital technologies. The study seeks to recommend a strategy for wider access to library services to promote diversity of collections and inclusivity.
Keywords: Resource sharing; Digital divide; Southern Africa; Access to information; Library consortium